2018
DOI: 10.1371/journal.pone.0189936
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial voltage, circulating biomarkers of fibrosis, and atrial fibrillation ablation. A prospective cohort study

Abstract: AimsTo test the ability of four circulating biomarkers of fibrosis, and of low left atrial voltage, to predict recurrence of atrial fibrillation after catheter ablation.BackgroundCirculating biomarkers potentially may be used to improve patient selection for atrial fibrillation ablation. Low voltage areas in the left atrium predict arrhythmia recurrence when mapped in sinus rhythm. This study tested type III procollagen N terminal peptide (PIIINP), galectin-3 (gal-3), fibroblast growth factor 23 (FGF-23), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 15 publications
1
34
1
8
Order By: Relevance
“…Among the 38 full‐text articles assessed for eligibility, ten were excluded for the following reasons: One study lacked a control group; one study population was heart failure; four studies lacked available data for further analysis; and four reported duplicate data from studies that later published as full text . Finally, 28 studies involving 10 830 patients were included in our meta‐analysis, with their baseline characteristics shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 38 full‐text articles assessed for eligibility, ten were excluded for the following reasons: One study lacked a control group; one study population was heart failure; four studies lacked available data for further analysis; and four reported duplicate data from studies that later published as full text . Finally, 28 studies involving 10 830 patients were included in our meta‐analysis, with their baseline characteristics shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Reports on the use of biomarkers in predicting successful ablation are inconsistent as well as only partially positive. [29][30][31] The most positive results were observed in patients with nonparoxysmal AF and enlarged LA. 32 We did not observe any relationship between biomarkers of fibrosis and LAPA both in SR and AF, although our SR subgroup consisted mainly of paroxysmal AF patients with normal or slightly enlarged LA and AF subgroup was very small.…”
Section: Discussionmentioning
confidence: 96%
“…and AF. [29][30][31] The most positive results were observed in patients with nonparoxysmal AF and enlarged LA. Therefore, it cannot be used for selecting candidates for RFCA or establishing prognosis prior to procedure.…”
Section: Relationship Between Lapa and Biomarkers Of Fibrosismentioning
confidence: 96%
“…Nevertheless, other studies failed to verify the correlation between these biomarkers and fibrosis as assessed by LA low-voltage area (Begg et al, 2017). A convincing explanation is that the blood levels of fibrosisrelated biomarkers are susceptible to non-cardiac fibrosis, and systemic fibrosis masks their peripheral levels (Begg et al, 2018). In our study, we pre-excluded patients with severe heart failure and those with autoimmune or infectious diseases; only patients newly diagnosed with PAF were included.…”
Section: β1arabs In Af Patientsmentioning
confidence: 93%